TEACHERS TOWARDS COMMUNICATION AND INFORMATION TECHNOLLOGIES INTRUTION IN SCHOOL SCENARIO - Vesga, Luz del Sol; Vesga, Juanita del Mar (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
Research’s main approach is based on social highlights on Information and Communication Technologies of elementary school teachers in a school located in a marginal side of urban area at Popayan (Cauca, Colombia). This research is mainly qualitative and is based on fundamental theorical method, taking as starter all experiences and life facts of these teacher’s personal daily basis towards introduction and use of new technologies in school contexts, leading into analysis and final digitalization of all stories in which feelings and beliefs built by teachers upon responding settings towards new technologies in scholar field were discovered.